Toxoplasma gondii exposure in Brazilian indigenous populations, their dogs, environment, and healthcare professionals - Doline, Fernando Rodrigo; Farinhas, João Henrique; Biondo, Leandro Meneguelli; de Oliveira, Pollyanne Raysa Fernandes; Rodrigues, Nássarah Jabur Lot; Patrício, Karina Pavão [UNESP]; Mota, Rinaldo Aparecido; Langoni, Helio; Pettan-Brewer, Christina; Giuffrida, Rogério; Santarém, Vamilton Alvares; de Castro, Wagner Antônio Chiba; et al. (Elsevier, 2023)
Although Toxoplasma gondii exposure has been reported in indigenous populations worldwide, a One Health approach has not been applied to date. This study concurrently assessed T. gondii exposure in indigenous populations, and their dogs, environment, and indigenous or non-indigenous healthcare professionals (HPs). Human and dog serum samples from 9 indigenous communities in Brazil were assessed by indirect immunofluorescence antibody test for anti-T. gondii antibodies. Soil samples (30 per community) were processed with PCR to amplify T. gondii DNA. Associated risk factors and seroprevalence were analyzed using logistic regression models. Human seropositivity and type of water source were assessed by generalized linear mixed model (GLMM) with binomial error distribution, and game meat consumption with chi-squared test. Overall, 225/463 (49%) indigenous persons were seropositive for anti-T. gondii antibodies. Of all the HPs, 67/168 (40%) were positive, and included 54/147 (37%) positive non-indigenous HPs. Indigenous persons more likely to be seropositive compared with non-indigenous HPs (OR: 1.63; 95% CI: 1.11–2.39). A total of 97/253 (38%) dogs were seropositive and highly associated with seropositive owners (p < 0.001). Based on univariate analysis for indigenous individuals, state location of community (p < 0.001), ethnicity (p < 0.001), consumption of game meat (p < 0.001), type of water source (p < 0.001), and educational level (p = 0.026) were associated with seropositivity. Logistic regression showed that indigenous seropositivity was associated with eating game meat (p = 0.002), drinking water from rivers (p < 0.001), and inversely proportional to the educational level. According to univariate analysis for non-indigenous HP, age (p = 0.005), frequency of visits to the indigenous populations (p < 0.001), consumption of water at the indigenous communities (p < 0.001), and ingestion of raw meat (p = 0.023) were associated with T. gondii seropositivity. Logistic regression revealed living outdoors (p = 0.042), habit of hunting (p = 0.008), and drinking river water (p = 0.007) as risk factors associated to seropositivity in dogs. In addition, indigenous communities lacking water treatment had higher seroprevalence for all groups including indigenous persons (GLMM; z = −7.153; p < 0.001), their dogs (GLMM; z = −2.405; p = 0.0162), and all HPs (GLMM; z = −2.420; p = 0.0155). Human seropositivity was associated with that of their dogs (p < 0.001). A single soil sample, out of 270 (0.37%), was positive for T. gondii by PCR. Our results indicate water source is a risk for human and dog toxoplasmosis in indigenous communities; both share similar exposure. Moreover, quality water access was shown to be crucial to prevent toxoplasmosis in both total and non-indigenous HPs who work in these indigenous communities.
Keywords: Health inequities; Public health; Water quality